Small Discussion Method: Peningkatan Kompetensi Guru Madrasah Tsanawiyah Binaan Kota Yogyakarta dalam Menerapkan Model Cooperative Learning - Murtinah Murtinah (Jurnal Pendidikan Madrasah, 2019)
The weak teacher's competence in understanding learning models is an early cause of student achievement in the mastery of teaching materials. A weak symptom of the teacher's understanding of the learning model at MTs Muhammadiyah Karangkajen in understanding the learning model was found after the academic supervision of one semester in the first semester of lesson 2019/2020. This research aims to determine the extent to which the professional improvement of teachers through small discussion in understanding and implementing cooperative learning models in order to improve student learning achievement. This research using the method of study of Madrasah (PTS) is conducted in 2 cycles. Improved teacher competence in understanding and implementing cooperative learning models achieve satisfactory results. From a pre 41.43% cycle, it becomes 71.43% on the I cycle, and can increase to 80.33% in the II cycle. The results of this study show that coaching through academic supervision through small discussion can improve the professionalism and performance of teachers in understanding cooperative learning models with a 80% compensation.